2004
DOI: 10.1007/s00442-004-1781-2
|View full text |Cite
|
Sign up to set email alerts
|

Demography in relation to population density in two herbivorous marsupials: testing for source?sink dynamics versus independent regulation of population size

Abstract: We compared demography of populations along gradients of population density in two medium-sized herbivorous marsupials, the common brushtail possum Trichosurus vulpecula and the rufous bettong Aepyprymnus rufescens, to test for net dispersal from high density populations (acting as sources) to low density populations (sinks). In both species, population density was positively related to soil fertility, and variation in soil fertility produced large differences in population density of contiguous populations. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…Our estimated densities were much lower than those recorded in wetter areas, east of the great dividing range in the Townsville region, but huge variation in densities have been recorded in relation to soil fertility (Johnson, Vernes & Payne, 2005). The home range of rufous bettongs is also highly variable, from 15 to 107 ha, suggesting that at our 1041 ha study location there was likely home range overlap between the 46 individuals we marked (Frederick & Johnson, 1996;Johnson et al, 2005). In 2015, the driest year of the study, breeding was not observed and estimated survival rates were low.…”
Section: Discussioncontrasting
confidence: 86%
“…Our estimated densities were much lower than those recorded in wetter areas, east of the great dividing range in the Townsville region, but huge variation in densities have been recorded in relation to soil fertility (Johnson, Vernes & Payne, 2005). The home range of rufous bettongs is also highly variable, from 15 to 107 ha, suggesting that at our 1041 ha study location there was likely home range overlap between the 46 individuals we marked (Frederick & Johnson, 1996;Johnson et al, 2005). In 2015, the driest year of the study, breeding was not observed and estimated survival rates were low.…”
Section: Discussioncontrasting
confidence: 86%
“…Several studies of Australian marsupials have found links between indices of quantitative habitat quality and density (Braithwaite et al . 1984; Johnson et al . 2005) but through the indirect link of foliar or soil nutrient levels rather than food abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Fox area (northern Queensland, Australia, see Fig. 1) found that over a 3‐year period both high‐ and low‐density populations showed little variation in size, similar rates of turnover and no evidence for net dispersal from high‐ to low‐density populations (Johnson et al . 2005).…”
Section: Introductionmentioning
confidence: 99%